The relationship between the socio-environmental problems of the twenty-first century and the Covid-19 pandemic - dos Santos , Maria das Dores; Bampi , Aumeri Carlos; Buhler, Helena Ferraz (Seven Editora, 2024)
COVID-19 is infectious, of zoonotic origin and rapid spread. Among the measures adopted to contain the advance of the disease, the interruption of human activities stood out, such as the closure of industries and transport, actions that proved to be positive for the environment and human health, reflecting in achievements such as the reduction of pollution and respiratory diseases. Several factors have been pointed out for the emergence/re-emergence, emergence and resurgence of infectious diseases, including population growth that intensifies the process of urbanization, globalization, loss of biodiversity, deforestation and land use change. This study aimed to verify the relationship between the socio-environmental problems of the twenty-first century, with a focus on deforestation and the change in land use with the emergence of the COVID-19 pandemic. This is a narrative review of the literature carried out in the databases of CAPES, SCIELO, PUBMED, GOOGLE SCHOLAR and national and international news sites and public organizations such as the World Health Organization and the Ministry of Health. The analysis of these studies allowed the creation of three categories, namely: 1) Advance of deforestation in Brazil and in the world; 2) Climate change; and 3) Human interference and COVID-19. Deforestation is a human activity associated with the emergence of zoonotic diseases, used to open and expand areas for agriculture and livestock. The practice has brought humans and domestic animals closer to wildlife, in this sense, it dialogues with another situation that is related to the theme expanded in this work, the illegal trafficking of wild animals. The highlighted conditions increase the risks of exposure to pathogens, which may favor the emergence of emerging diseases, such as COVID-19. DOI:https://doi.org/10.56238/sevened2024.025-015